PLIO-PLEISTOCENE FOSSIL VERTEBRATES OF MONTE TUTTAVISTA (OROSEI, EASTERN SARDINIA, ITALY), AN OVERVIEW (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The preliminary results of the analisys of fossil vertebrate remains from 19 fissure fillings in the karst network at Monte Tuttavista (Orosei, NMoro) are reported. about 80 taxa, among fishes, amphibians, reptiles, birds and mammals have been recognised.These remains document the evolution of vertebrate assemblages in the Sardinian insular domain, during a time interval apparently spanning the Late Pliocene to Late Pleistocene or Holocene. A succession of at least four populating complexes has been identified which document the vertebrate colonisation phases from the Italian mainland and the following periods of insularity. Indeed, the occurrence of endemic taxa such as the murid Rhagapodemus minor, the primate Macaca cf. M. majori and the caprine Nesogoral, suggest some fissure fillings date to a phase close to the Plio/Pleistocene boundary since these taxa occur at the Sardinian locality Capo Figari I which has been dated to about 1.8 Ma. However, the presence of the "hunting-hyaena" Chasmaporthetes, never reported before in Sardinia, could suggest that the beginning of the vertebrate record of Monte Tuttavista is older, given that this carnivore is documented in European Middle Pliocene-Early Pleistocene localities. The vertebrate assemblages that document the most recent migratory phases in the karst network of Monte Tuttavista are characterised by the occurrence of the endemic megalocerine cervid Praemegaceros cazioti and the arvicolid Tyrrhenicola henseli which are comparable with those occurring in other Late Pleistocene and early Holocene Sardinian sites.